Woman Participation in Politics: Toward an Ideal Model in the Perspective of Siyasa al-Shar'iyya - Ramli, Angraini binti; Elatrash, Radwan Jamal (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2021)
Women’s opinions and welfare are not adequately represented and often disregarded. Even though female populations are increasing in every country, it did not automatically make it a strong reason for them to represent themselves in politics or any governance structure. The equality to take part in the public field and voice out their opinions is always underestimated by some parties with misunderstanding religious statements. By this problem, this article aims to see the statistics of women's participation in politics, their roles, and the barriers found then discuss an ideal model of women's participation from Siyāsa al-Shar`iyya’s perspective. By using an inductive and analytical method to examine several sources from books, articles, and journals, and after that draw the conclusion that the country has provided an equal right for all citizens. It is in harmony with Islam that perceives the equality of all servants without any ethnic and gender differences. Women’s involvement in politics aims to ensure a good representation of their aspirations. The available barriers did not come from religious factors but from a patriarchal system that is well embedded in the society as a culture.